2018
DOI: 10.1177/1120672117750059
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of internal limiting membrane peeling with and without foveal sparing in myopic foveoschisis

Abstract: Vitrectomy with complete internal limiting membrane peeling resulted in comparable outcomes to those achieved with preservation of the epi-foveal membrane in treating cases with myopic foveoschisis. There was no statistically significant difference in final visual acuity between the two groups. No macular holes were recorded in either group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…By screening titles and abstracts, 20 studies were excluded. Finally, six studies [16][17][18][19][20]23 in English were eligible for this meta-analysis by assessing full text (Figure 1). Non-randomized and retrospective studies were included.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By screening titles and abstracts, 20 studies were excluded. Finally, six studies [16][17][18][19][20]23 in English were eligible for this meta-analysis by assessing full text (Figure 1). Non-randomized and retrospective studies were included.…”
Section: Search Resultsmentioning
confidence: 99%
“…In recent years, there are several studies focusing on this technique. Elwan et al 17 found no superiority of fovea-sparing ILM peeling. Given that the sample sizes were small, the pooled data would contribute to more reliable outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…Such adverse events may be even more common in pathological myopia, characterized by long axial length and diffuse chorioretinal atrophy. To prevent postoperative macular hole formation and possible damage to the fovea, a fovea-sparing ILMP technique has been advocated [8,19,20], but some studies have shown that there is no difference in postoperative visual acuity between fovea-sparing ILMP and complete ILMP [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Many subsequent studies have demonstrated that vitrectomy with internal limiting membrane peeling (ILMP) can be effective in producing both anatomical and functional improvement in MF [3][4][5][6][7]. In order to reduce postoperative macular hole (MH) formation and foveal damage, a partial ILMP technique with foveal sparing was proposed [8], but there is little evidence that this technique has better outcomes than complete ILMP [9,10] Furthermore, more recent studies have shown similar anatomical and functional improvements can be achieved without any form of IMLP [4,11], casting doubt on the benefits of ILMP.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous surgical options for the treatment of foveoschisis have been reported (27). A number of studies have suggested the benefits of vitrectomy for the resolution of foveoschisis by removing vitreoretinal traction (28,29). However, the evidence supporting the need to peel the ILM is inconsistent.…”
Section: Discussionmentioning
confidence: 99%